Factors influencing maternal-fetal attachment in pregnant women during the COVID-19 pandemic: a cross-sectional study - Hyeryeong Yoon; Hyunkyung Choi (Korean Society of Women Health Nursing, 2023)
Purpose Coronavirus disease 2019 (COVID-19) has spread widely throughout the world, causing psychological problems such as fear, anxiety, and stress. During the COVID-19 pandemic, pregnant women have been concerned about both their own health and the health of their fetuses, and these concerns could negatively affect maternal-fetal attachment. Thus, this study aimed to explore the level of COVID-19 stress, resilience, and maternal-fetal attachment among pregnant women during the COVID-19 pandemic, and to identify factors influencing maternal-fetal attachment. Methods In total, 118 pregnant women past 20 weeks gestation were recruited from two maternity clinics in Daegu, Korea, to participate in this descriptive correlational study during COVID-19. The factors influencing maternal-fetal attachment were analyzed using hierarchical multiple regression analysis. Results The mean scores for COVID-19 stress, resilience, and maternal-fetal attachment were 57.18±10.32 out of 84, 67.32±15.09 out of 100, and 77.23±9.00 out of 96, respectively. Nulliparous pregnant women reported greater maternal-fetal attachment than multiparous pregnant women (p=.003). Religious pregnant women also reported greater maternal-fetal attachment than non-religious pregnant women (p=.039). Resilience (β=.29, p=.002), COVID-19 stress (β=.20, p=.030) and parity (β=-.17, p=.047) were factors influencing maternal-fetal attachment, and these factors explained 26.4% of the variance in maternal-fetal attachment (F=10.12, p<.001). Conclusion Converse to common sense, COVID-19 stress exerted a positive influence on maternal-fetal attachment in pregnant women during the COVID-19 pandemic. Healthcare providers need to recognize the positive influence of COVID-19 stress and implement intervention strategies to strengthen resilience in pregnant women to improve maternal-fetal attachment.